Specific Issues of Arctic Cruise Development in the Russian Arctic: the Russian Arctic National Park Case Study - Kruzhalin, Victor; Shabalina, Natalia; Kashirina, Ekaterina; Nikanorova, Alexandra (Anais Brasileiros de Estudos Turísticos, 2022)
The specific issues of the arctic cruise development are highlighted for the Russian Federation. The research is based on data obtained during the expedition (July-August 2021) in the Russian Arctic National Park, located within Franz Josef Land and Novaya Zemlya archipelagoes. The research was carried out in order to evaluate the prospects for the development of cruise tourism and identify the risks of implementing projects for the development of cruise tourism in the Russian Arctic National Park as more available for tourism territory than other Russian arctic islands. The national park is considered as a prospect site for arctic cruises operation according with the State interests to develop the Arctic zone of the Russian Federation as well. Results and conclusion evidence the potential of tourism as well as describe the specific factors hindering the development of tourism there. They are associated with the peculiarities of the climate, weather and natural phenomena, the vulnerability of landscapes to anthropogenic loads and administrative and legal barriers.